44.6k views
0 votes
What is the solution to the system of equations?

X - 3y – Z=-9
-2x + y + 2z = 3
2x + y + 3z = 8

1 Answer

7 votes

Answer:

x = 1 y = 3 z = 1

Explanation:

(1) x - 3y - z = -9 (2) -2x + y + 2z = 3 (3) 2x + y + 3z = 8

2x(1) 2x - 6y - 2z = -18 (2) -2x + y + 2z = 3

- 5y = -15 2y + 5z = 11

y = 3 2(3) + 5z = 11

6 + 5z = 11

5z = 5

z = 1

x - 3(3) - 1 = -9

x - 9 - 1 = -9

x - 10 = -9

x = 1

Note: If you write your equations across your paper, then the work can just flow down the paper. It makes it so much easier to show the work you have done. OK?

User Thesmart
by
5.1k points